Improving the Students’ Vocabulary Mastery by Using Word Cloud at The Tenth Grade of SMK Negeri 1 Gunungsitoli In 2022/2023 - Arlina Laoli; Yasminar Amaerita Telaumbanua; Adieli Laoli; Afore Tahir Harefa (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
Vocabulary mastery is a skill that refers to a high level of proficiency in processing words in a language. The students at the tenth grade of SMK Negeri 1 Gunungsitoli lacked vocabulary mastery, so they found it difficulty to understand texts properly and did not achieve the minimum competency criteria (MMC) that has been set at school. The purpose of this study was to improve the students' ability to vocabulary mastery. In improving students' vocabulary mastery, the researcher used Word Cloud and applied it in Classroom Action Research (CAR). This research was conducted in Cycle II, there were four steps in conducting research, namely: planning, action, observation and reflection. . In Cycle I, there was no student who was classified in "very good level", there were two students (5.72%) in "good level". Instead of that, there were 19 students (54.28%) in "fair level", 14 students (40%) in "poor level". In addition, the average of the students' mark was 53.00. The results show that many students were at enough and less levels so it really needed to be improved in the next cycle. In Cycle II, there was 1 student (2.86 ) in “poor level”, there were 7 students (20%) in “fair level”, there were 6 students (17.14%) in “good level”, and 22 students ( 62.86 % ) in “very good level”. In addition, the average of the students' mark was 86.42. The students' average mark was higher than the MMC that was 75. Based on the explanation above, it is concluded that the Word Cloud can improve the students' vocabulary mastery at the tenth grade of SMK Negeri 1 Gunungsitoli in 2022/2023. Keywords: Vocabulary Mastery, Word Cloud, CAR